2008
DOI: 10.1111/j.1751-3928.2008.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Re‐Os Geochronology of Mineralization of the Miduk Porphyry Copper Deposit, Iran

Abstract: The Miduk porphyry copper deposit is located in Kerman province, 85 km northwest of the Sar Cheshmeh porphyry copper deposit, Iran. The deposit is hosted by Eocene volcanic rocks of andesitic -basaltic composition. The porphyry-type mineralization is associated with two Miocene calc-alkaline intrusive phases (P1 and P2, respectively). Five hypogene alteration zones are distinguished at the Miduk deposit, including magnetite-rich potassic, potassic, potassic -phyllic, phyllic and propylitic. Mineralization occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 32 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Igneous activity in this zone started in the Eocene (50 Ma) and continued to a climax during the middle Eocene for exposed volcanic rocks and Oligo-Miocene for plutonic rocks in many parts of Iran (Berberian and King, 1981). These volcanic and plutonic rocks are generally associated with porphyry copper and skarn mineralization in the Sahand-Basman zone, including deposits such as Sungun (Hezarkhani and Williams-Jones, 1998), Sarcheshmeh (Waterman and Hamilton, 1975;Shahabpour, 1982;Hezarkhani, 2006), Miduk (Hassanzadeh, 1993;Taghipour et al, 2008), and many other subeconomic ore bodies (Zarasvandi et al, 2005) The geology of the Dehaj-Sarduiyeh district mainly consists of an Upper CretaceousEocene basic to felsic volcanic-sedimentary complex. Oligo-Miocene granitic rocks intruded into thick sequences (as thick as 15 km) of Eocene lava, pyroclastic, and volcaniclastic rocks as batholiths, stocks, and dykes.…”
Section: Geologic Settingmentioning
confidence: 95%
See 2 more Smart Citations
“…Igneous activity in this zone started in the Eocene (50 Ma) and continued to a climax during the middle Eocene for exposed volcanic rocks and Oligo-Miocene for plutonic rocks in many parts of Iran (Berberian and King, 1981). These volcanic and plutonic rocks are generally associated with porphyry copper and skarn mineralization in the Sahand-Basman zone, including deposits such as Sungun (Hezarkhani and Williams-Jones, 1998), Sarcheshmeh (Waterman and Hamilton, 1975;Shahabpour, 1982;Hezarkhani, 2006), Miduk (Hassanzadeh, 1993;Taghipour et al, 2008), and many other subeconomic ore bodies (Zarasvandi et al, 2005) The geology of the Dehaj-Sarduiyeh district mainly consists of an Upper CretaceousEocene basic to felsic volcanic-sedimentary complex. Oligo-Miocene granitic rocks intruded into thick sequences (as thick as 15 km) of Eocene lava, pyroclastic, and volcaniclastic rocks as batholiths, stocks, and dykes.…”
Section: Geologic Settingmentioning
confidence: 95%
“…Tiny grains of other ore minerals are bornite and enargite. Based on Re-Os dating of molybdenite, the hypogene mineralization formed at 12.23 ± 0.07 Ma ( (Taghipour et al, 2008).…”
Section: Mineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The orebody contains 170 million tons of ore, with an average grade of 0.86 % Cu, 0.007 % Mo, 82 ppb Au and 1.8 ppm Ag. Supergene enrichment blankets average approximately 50 m thickness and comprise the primary source of Cu ore (Taghipour et al 2008).…”
Section: Case Descriptionmentioning
confidence: 99%
“…Stöcklin (1968) and Aghanabati (1990)] and location of Chahfiruzeh and Sarcheshmeh porphyry systems. Hamilton, 1975), andesitic dykes in Sungun (Hezarkhani, 2006), and diorite-to quartz-diorite dykes in Miduk (Taghipour et al, 2008). Hasanpour (2010) showed that the andesitic dykes in Sungun postdated the main stage of alteration-mineralization by less than 0.5 Ma.…”
Section: Introductionmentioning
confidence: 99%